Ekonomi Indonesia Mengatasi Tantangan, Menjaga Stabilitas - Buke, Josua Logo; Suna, Agnes Elisabet Diva; Meni, Mariana Ratu Rosario; Dima, Enike Tje Yustina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Indonesia, as one of Southeast Asia’s largest economies, continues to face significant challenges in maintaining macroeconomic stability amid ongoing global uncertainties. This study aims to analyze the main economic issues impacting Indonesia in early 2025, including geopolitical instability, inflation, dependence on primary commodity exports, and fiscal pressures. The objective is to identify how government policies respond to these challenges to ensure resilient and inclusive economic growth. Using a qualitative approach through literature review, this research collects and analyzes secondary data from academic journals, economic reports, and policy documents. The content analysis method is employed to interpret the information and extract relevant insights. The findings show that despite a slight slowdown, the Indonesian economy grew by 4.87% in the first quarter of 2025, accompanied by a decline in the open unemployment rate to 4.76%. The government has implemented strategic measures such as optimizing the State Budget (APBN), conducting structural reforms, accelerating digital transformation, and enhancing fiscal and monetary coordination. These efforts contribute to maintaining purchasing power, improving investment climate, and strengthening national economic resilience. This study highlights the importance of proactive and integrated policy responses in navigating external pressures and achieving sustainable development goals.